2006
DOI: 10.12968/hmed.2006.67.sup5.21077
|View full text |Cite
|
Sign up to set email alerts
|

Radial arterial lines

Abstract: Intra-arterial cannulae in the radial artery are used for invasive arterial blood pressure (IABP) measurement and for collection of blood for analysis. The radial artery is the preferred site for insertion because of low complication rates. Arterial lines are the gold standard for accurate blood pressure (BP) measurement. They may be used in intensive care units (ICU) and high dependency units and in anaesthetized patients undergoing surgical procedures. An understanding of basic principles enables arterial li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…One article had a companion video to demonstrate the procedural steps but provided no specific checklist, 2 while 4 other articles described the procedure in paragraph form. [7][8][9][10] Multiple articles were found that pertained to radial arterial line insertion used for cardiac catheterization. Cohen and Alfonso 15 describe a radial arterial line placement curriculum within the context of radial access for cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One article had a companion video to demonstrate the procedural steps but provided no specific checklist, 2 while 4 other articles described the procedure in paragraph form. [7][8][9][10] Multiple articles were found that pertained to radial arterial line insertion used for cardiac catheterization. Cohen and Alfonso 15 describe a radial arterial line placement curriculum within the context of radial access for cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…One article had a companion video to demonstrate the procedural steps but provided no specific checklist, 2 while 4 other articles described the procedure in paragraph form. 7-10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation